Perbandingan Kejadian dan Faktor Risiko Hipertensi antara RW 18 Kelurahan Panembahan dan RW 1 Kelurahan Patehan - Cindy Cekti, Adiguno S.W., Sarah A.H., Khoirul A., Mohammad E.P., Datu R., Dyah A.R., Ika (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: The elderly makes up 10.9% and 15.5% of 720 residents in RW 18 Kelurahan Panembahan and 645 residents in RW 1 Kelurahan Patehan, respectively. Most of the elderly in both RW districts suffer from hypertension and ranks at third place among the 10 most prevalent diseases in Puskesmas Kraton in 2006. The prevalence of hypertension cases always increases year after year in both kelurahan. Therefore, hypertension gets more concern and support from stakeholders (the government, puskesmas, LSM) in the attempts of prevention and control, both in the form of health promotions and therapy.Objective: To determine the incidence of hypertension, the level of awareness of the residents, and the risk factors that affect the elderly in RW 18 Kelurahan Panembahan and RW 1 Kelurahan Patehan, Kecamatan Kraton.Method: This research is a descriptive observational study, with cross-sectional study design. The research subjects are the people within the society of Kelurahan Patehan and Kelurahan panembahan aged >60 years old. The numbers of samples obtained are 110 respondents. The instruments of this research are: calibrated aneroid sphygnomanometer, weighing scale, measuring tape, and questionnaires. Data analysis is done with the Chi-square test method and Fisher Exact test by using crosstabs, in addition to using the compare mean independent T-test.Results: Hypertension is found to affect 59.3% of the elderly population in RW 1 Patehan and 55.36% of thepopulation in RW 18 Panembahan. Interestingly, this corresponds to the prevalence data collected by JNC VII which states that half of the population aged 60-69 years old suffers from hypertension. Further analysis done within this research shows that there is no significant correlation between the incidence of hypertension and the risk factors of BMI, smoking, exercise, diets with high salt content, and coffee. In RW 18 Kelurahan Panembahan, the p values for the risk factors mentioned above are 0.159; 1.000; 1.000; 0.367; and 0.446 respectively. In RW 1 Kelurahan Patehan, the p values are 0.181; 1.000; 0.901; 1.000; and not analyzable. Based on interview, the amount of salt consumption in both RW is somewhat difficult to determine in the field, as the food is cooked and prepared in each household for several family members at a time. It is difficult for the subjects to estimate how many tablespoonfuls of salt is used in the dishes because subjects are accustomed to use rough hand measurements in taking salt. In addition to that, parts of the society in the target environment prefer to buy instant foods. The same applies to coffee consumption; it is hard to estimate the amount consumed because it is not a routine activity, and each individual differs in the sense of how much coffee taken each day and which type of coffee is used. The consumption of cigarettes everyday also differs between one individual and the other and the average amount is below that which can cause increase in blood pressure.Conclusion: The quantitative study in this research, supported with a qualitative study, shows that aspects of behavior are not risk factors that can cause hypertension. The incidence of hypertension in Kelurahan Patehan and Panemahan is related to age. Therefore, research is done regarding age distribution and hypertension incidence in the region, preceded by improvements in the instruments used to determine the levels of salt and caffein consumption and levels of stress. The residents of RW 1, Kelurahan Patehan and RW 18, Kelurahan Panembahan, Kecamatan Kraton may serve as models to illustrate that there is no correlation between risk factors and incidence of hypertension in an urban area with high levels of stress. Therefore, there is the need to do further research regarding cultural (Kraton) influences city toward another city center settlements stress factors that are related to hypertension.Keywords: elderly, hypertension, risk factors, Kelurahan Patehan and Panembahan, Kecamatan Kraton